The Relationship Between Managerial Style, the School Climate, and Persistence in High Schools Among the Arab Community of Israel: Students’ persistence and managerial style - Assadi, Nabil; Hibi, Wafiq (Advances in Social Sciences Research Journal, 2021)
The current study examines the relationship between the style of management and the school climate and the persistence in secondary schools in Arab society. Although studies have been carried out in Israel and abroad, few have focused on examining the subject in Arab society. The current study will focus on key issues concerning the impact of the ethical climate and managerial style on this phenomenon. The main research question in the current study is whether there is a link between the school ethical climate and management style and the persistence of students in secondary schools in Arab society. The findings of the study show that schools with a more caring ethical climate have a higher persistence rate and accordingly, the lower the caring ethical climate, the lower the percentage of persistence in school. It also indicates that the more focused the style on human relations, the more caringf the climate will be, and the more mission-focused the style, the more instrumental the ethical climate will be. The findings also indicate that there is a positive relationship between a management style focused on human relations and persistence. The conclusion of the main study indicates a positive relationship between a management style focused on human relations and a caring climate and the persistence of secondary school students in Arab society. A management style based on positive, humanitarian relationships focused on cooperation between principals and teachers allows for similar relationships between teachers among themselves. patterns of cooperation and mutual support are developed instead of competition and striving against each other, allowing for the creation of a more caring ethical climate.